Medialna rzeczywistość w „Truman Show” (1998) Petera Weira w perspektywie myśli gnostyckiej - Kwiatkowski, Fryderyk (Collectanea Philologica, 2015)
In the author’s opinion the story depicted in "The Truman Show" (1998) by Peter Weir comprisesa reinterpretation of a Gnostic myth about the liberation of a „divine spark” from the material world.In spite of the fact that the director did not know about Gnosticism before he started to make the film,the author of the article presents that many motifs in his work can be viewed through the ideas expressedin various Gnostic systems. The Gnostic notions were reinterpreted in "The Truman Show" on a fundamentallevel of the world being presented in as well as in the narrative structure of the movie.